Pomen anonimne arhitekture historičnega mestnega jedra Kopra v prenovitvenih postopkih - Kovač, Mojca M. (Zbornik za umetnostno zgodovino (Nova vrsta), 1998)
The aim of this contribution is to emphasise the importance of the services for the protection of memorials in the process of comprehensive restoration of historical city centres and to emphasise the active role which they should play, in conjunction with the other professions involved; here the most important thing is the need to develop and adopt a methodological approach to the treatment of anonymous architecture in such as way as to achieve the best possible results. The study begins with a short survey of the development of the professionalisation of the protection of monuments ...
Keywords: spomeniško varstvo; architecture; arhitektura; mestna jedra; Koper